2014
DOI: 10.1681/asn.2013101122
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Kidney Disease and Cancer after Renal Transplantation

Abstract: Autosomal dominant polycystic kidney disease (ADPKD), the most common form of polycystic kidney disease (PKD), is a disorder with characteristics of neoplasia. However, it is not known whether renal transplant recipients with PKD have an increased risk of cancer. Data from the Scientific Registry of Transplant Recipients, which contains information on all solid organ transplant recipients in the United States, were linked to 15 population-based cancer registries in the United States. For PKD recipients, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 25 publications
1
45
0
1
Order By: Relevance
“…After multivariable adjustment, overall cancer incidence was found to be significantly lower in patients with ADPKD by about 16%-17%, suggesting that there is cancer protection associated with PKD. 46 This was also found to be true for ARPKD, in a study that examined the incidence of colon cancer in unaffected carriers of a recessive PKHD1 mutation. 47 The reason for the lower cancer risk in patients with ADPKD is not known, but may relate to biologic characteristics of ADPKD itself or to better cancer risk behaviors with these patients.…”
Section: Neoplastic Cyst Growth-but Why Not Cancer?mentioning
confidence: 82%
See 1 more Smart Citation
“…After multivariable adjustment, overall cancer incidence was found to be significantly lower in patients with ADPKD by about 16%-17%, suggesting that there is cancer protection associated with PKD. 46 This was also found to be true for ARPKD, in a study that examined the incidence of colon cancer in unaffected carriers of a recessive PKHD1 mutation. 47 The reason for the lower cancer risk in patients with ADPKD is not known, but may relate to biologic characteristics of ADPKD itself or to better cancer risk behaviors with these patients.…”
Section: Neoplastic Cyst Growth-but Why Not Cancer?mentioning
confidence: 82%
“…As such, we carried out an epidemiologic study to answer this question. 46 Data from the Scientific Registry of Transplant Recipients, which contains information on all solid organ transplant recipients in the United States, were linked to 15 populationbased United States cancer registries that included data on 50 different cancers. Cancer incidence was compared in PKD versus non-PKD renal transplant recipients, and incidence rate ratios adjusted for age, sex, race/ethnicity, dialysis duration, and time since transplantation were determined.…”
Section: Neoplastic Cyst Growth-but Why Not Cancer?mentioning
confidence: 99%
“…On the other hand, increased apoptosis in ADPKD may counteract hyperproliferation, which may prevent kidneys from progression of PKD into the renal cell carcinoma despite the high rate of epithelial cell proliferation. Recent retrospective study showed that cancer incidence was lower in PKD renal transplant recipients than in non-PKD renal transplant recipients (101). The exact mechanisms of the low cancer risk in PKD recipients are unclear, but may be associated with the increased apoptosis.…”
Section: The Role Of Apoptosis In Adpkdmentioning
confidence: 99%
“…First the findings were considered coincidental, but many case reports and case series have continued to support this hypothesis [7]. Some studies showed an incidence for RCC of up to 15% in surgically removed ADPKD kidneys, the majority of these tumours measuring less than 2 cm in size [7,10,11]. Table 1 Table 2: Literature Review, list of published ADPKD cases diagnosed with renal cell carcinoma (RCC).…”
Section: Commentarymentioning
confidence: 99%
“…In comparison to ADPKD, ESRD and its associated acquired renal cystic disease are well-established risk factors for RCC and have widely been accepted in the literature [11,14,15]. The prevalence of RCC in ESRD patients is significantly higher than the prevalence of sporadic RCC in the general population (by an estimated factor of 1000) [7].…”
Section: Commentarymentioning
confidence: 99%